Determinación de material particulado pm₁₀ y pm₂.₅ producto de la explotación de canteras en el sector san Rafael de la ciudad de Latacunga. - Zavala Medranda, Jennifer Jossenka (2020)
This present project determined the concentrations of particulate material PM₁₀ and PM₂.₅, in San Rafael Latacunga which is an area of influence for open mining activities, to execute it, a representative sampling of this pollutant in suspension was carried out with two particle sizes which are currently legislation in Ecuador, in this context, the study area was characterized where two sites were established for monitoring using the E-BAM equipment, which generated a real database. The analysis of the results showed significant variations in the concentrations of the suspended particles. The average data of PM₁₀ particulate material at the first monitoring point, San Rafael Sur (X: 764774; Y: 9893856; Z: 2763) was: 18 μg/m³ and 7.35 μg/m³ for PM₂.₅; Likewise, at the second sampling site, San Rafael Centro (X: 764661; Y: 9894611; Z: 2781), a value was obtained for PM₁₀ of 45 μg/m³ and for PM₂.₅ of 7.54 μg/m³. These values were compared with the Ministerial Agreement 097-A Air Quality Standard that establishes 100 μg/m³ for PM₁₀ and 50 μg/m³ for PM₂.₅, therefore they are within the maximum permissible limits. The results show an alert for the authorities and the population so that control and prevention strategies can be implemented focusing on the care of the environment and the health of people through a follow-up by the competent environmental authority.